Is religiosity a barrier to sexual and reproductive health risks? Results from a population-based study of young Croatian adults - Puzek, Ivan (Array, 2011)
Following the demise of socialism in 1989, religious identification substantially increased in most countries of Central, East, and Southeast Europe. Considering that there is evidence that religiosity is associated with reduced sexual risk taking among young people, this study explored associations between religiosity – assessed at three different levels (religious upbringing, personal religiosity, and social network religiosity) – and sexual risks among young Croatian adults. In addition, we examined whether religiosity predicted chlamydial infection among women and men aged 18-25. The data were collected in a national probability survey carried out in 2010 (n=1, 005). Overall, the effects of religiosity were sporadic, present primarily among women, and of small size. This lack of a sizeable impact of religiosity on young adults’ sexuality is likely related to a particular type of religiosity, characterized by individualized morality, found among young people in the country. Although Croatia seems to be one of the most religious countries in Europe, our findings suggest that promoting religious morality – as recently attempted by an abstinence-based educational program – is not an efficient approach to reducing sexual risks.